2020
DOI: 10.1371/journal.pone.0230574
|View full text |Cite
|
Sign up to set email alerts
|

Silico-tuberculosis, silicosis and other respiratory morbidities among sandstone mine workers in Rajasthan- a cross-sectional study

Abstract: Background Exposures to respirable crystalline silica causes silicosis, pulmonary tuberculosis, chronic obstructive pulmonary disease, lung cancer, autoimmune disorders and chronic renal disease. The aim of this study was to find out the prevalence of silico-tuberculosis, silicosis and other respiratory morbidities in sandstone mine workers in Jodhpur district of Rajasthan. Methods It was a cross-sectional study done in sandstone mines in Jodhpur. A total of 15 mines were selected. The sample size was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…In Pakistan, Leghari et al [ 6 ] described high prevalences of respiratory symptoms among stone-crushing workers. In India, studies among quartz stone grinders by Tiwari et al [ 30 , 31 , 32 , 33 ] and among sandstone crushers by Singh et al [ 34 , 35 ] and Rajavel et al [ 36 ] identified silicosis, silico-tuberculosis, and respiratory functional impairment in a high proportion of exposed workers, even at a young age. In Nigeria, Nwibo et al [ 37 ] studied 403 male and female stone quarrying workers [mean age 30 years (SD 9 years)] by means of a questionnaire, spirometry, and chest radiography, and they concluded (without having a control group) that stone quarrying may increase the risk of respiratory symptoms and impaired lung function.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, Leghari et al [ 6 ] described high prevalences of respiratory symptoms among stone-crushing workers. In India, studies among quartz stone grinders by Tiwari et al [ 30 , 31 , 32 , 33 ] and among sandstone crushers by Singh et al [ 34 , 35 ] and Rajavel et al [ 36 ] identified silicosis, silico-tuberculosis, and respiratory functional impairment in a high proportion of exposed workers, even at a young age. In Nigeria, Nwibo et al [ 37 ] studied 403 male and female stone quarrying workers [mean age 30 years (SD 9 years)] by means of a questionnaire, spirometry, and chest radiography, and they concluded (without having a control group) that stone quarrying may increase the risk of respiratory symptoms and impaired lung function.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, Leghari et al [6] described high prevalences of respiratory symptoms among stone-crushing workers. In India, studies among quartz stone grinders by Tiwari et al [30][31][32][33] and among sandstone crushers by Singh et al [34,35] and Rajavel et al [36] identified silicosis, silico-tuberculosis, and respiratory functional impairment in a high proportion of exposed workers, even at a young age. In Nigeria, Nwibo et al [37] studied 403 male and female stone quarrying workers [mean age 30 years (SD 9 years)] by means of a questionnaire, spirometry, and chest radiography, and they concluded (without having a control group) that stone quarrying may increase the risk of respiratory symptoms and impaired lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Paparan silika kristal respirable dapat menyebabkan silikosis, tuberkulosis paru, penyakit paru obstruktif kronik, kanker paru, gangguan autoimun dan penyakit ginjal kronis. 15 Kegiatan penambangan seperti pengeboran, pemotongan, dan penghancuran mineral dan batu yang mengandung kristal silika melepaskan silika bebas di lingkungan kerja. Penghirupan dan pengendapan partikel debu silika menghasilkan peradangan persisten bersama dengan pembentukan granuloma dan fibrosis jaringan paru-paru, mengakibatkan pengurangan kapasitas fungsional paru-paru.…”
Section: Hasil Dan Pembahasanunclassified